Effect of Annealing Temperature and Spin Coating Speed on Mn-Doped ZnS Nanocrystals Thin Film by Spin Coating - Noor Azie Azura, Mohd Arif; Chong, Chee Jiun; Sahbudin, Shaari (Hindawi Publishing Corporation, 2017)
ZnS:Mn nanocrystals thin film was fabricated at 300°C and 500°C via the spin coating method. Its sol-gel was spin coated for 20 s at 3000 rpm and 4000 rpm with metal tape being used to mold the shape of the thin film. A different combination of these parameters was used to investigate their influences on the fabrication of the film. Optical and structural characterizations have been performed. Optical characterization was analyzed using UV-visible spectroscopy and photoluminescence spectrophotometer while the structural and compositional analysis of films was measured via field emission scanning electron microscopy and energy dispersive X-ray. From UV-vis spectra, the wavelength of the ZnS:Mn was 250 nm and the band gap was within the range 4.43 eV-4.60 eV. In room temperature PL spectra, there were two emission peaks centered at 460 nm and 590 nm. Under higher annealing temperature and higher speed used in spin coating, an increase of 0.05 eV was observed. It was concluded that the spin coating process is able to synthesize high quality spherical ZnS:Mn nanocrystals. This conventional process can replace other high technology methods due to its synthesis cost